Functions of time type, curvature and causality theory - ATINDOGBE, CYRIAQUE; HOUNNONKPE, RAYMOND (My University, 2019)
In the present paper various necessary and/or sufficient conditions in terms of the existence and properties of quasi-time functions, semi-time functions and generalized time functions are provided to get different levels of the causal ladder in spacetimes. We also show several links between curvature conditions and causality.
Keywords: Causality; Causal hierarchy; Generalized time function; Quasi-time function Semi-time function Null convergence condition